Novel Hierarchical Fe(III)-Doped Cu-MOFs With Enhanced Adsorption of Benzene Vapor - Sun, Xuejiao; Gu, Xiulian; Xu, Wentao; Chen, Wen-Jie; Xia, Qibin; Pan, Xiaoyang; Zhao, Xiaojing; Li, Yi; Wu, Qi-Hui (Frontiers in Chemistry, 2019)
New hierarchical Fe(III)-doped Cu-MOFs (Fe-HK) were developed via introduction of Fe3+ ions during HKUST-1 synthesis. The obtained products were characterized by N2 adsorption, X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, FTIR spectroscopy, and thermal analysis. The adsorption isotherms and kinetics of benzene vapor were measured and consecutive adsorption–desorption cycles were performed. It was found that the hierarchical-pore Fe-HK-2 exhibited optimal textural properties with high BET surface area of 1707 m2/g and total pore volume of 0.93 cm3/g, which were higher than those of the unmodified HKUST-1. Significantly, the hierarchical-pore Fe-HK-2 possessed outstanding benzene adsorption capacity, which was 1.5 times greater than the value on HKUST-1. Benzene diffusivity of Fe-HK-2 was 1.7 times faster than that of parent HKUST-1. Furthermore, the benzene adsorption on Fe-HK-2 was highly reversible. The hierarchical-pore Fe-HK-2 with high porosity, outstanding adsorption capacity, enhanced diffusion rate, and excellent reversibility might be an attractive candidate for VOCs adsorption. This may offer a simple and effective strategy to synthesize hierarchical-pore MOFs by doping with other metal ions.